(untitled) (Fiep Bulletin - online, 2015)
The objective of the research is to compare which of the samples, Soccer players of Field or Colleges student have greater Angle Q in the knee? Femural angle Q is defined by Kuhn, et al (2002), Nester, et al, (2001), Livingston, et al (1999), "and the angle formed in the intersections of Anterior Superior Illiac Spine (A.S.I.S.), the medial point of Patela (PM) and the Tubercle of the Tibia (TT) ", forming two perpendicular lines in quadríceps. According to Livingston, et al, (1999), "the angle in Q above and the 15 20 degrees this directly associated with patelo-femurais syndromes constantly attack in football players for extrinsic and intrinsic factors of the modality". The research and of quantitative characteristic with sampling of 30 individuals, being, 15 Soccer players of Field and 15 Colleges student. The used methodology was the gauging with camera assuming a methodological error of 1 the 5 mm second metanálise of Nester, et al, (2001). The presented results demonstrate one strong significance in (ME) for (JFC) e (U), with high force (F=12,7) and significance assumed for (P<0,01), with what it corroborates with the findings of other authors. Answering the question of the objective, one high significance between the groups is predominant in Left Members possibly for the asymmetry of the Members and other factors as: a precarious accompaniment of the team to multidiscipline (coach physicist, physiotherapist and nutritionist), that he can not be being carried through or has not demonstrated effectiveness in the analyzed factors. A form to correlate another data with Angle Q is the Densitömetria Óssea, that they corroborate with the citation of Kuhn, et al (2002), that they tell "abnormal dynamic in the bones of course cause a hipertrofic with increase of the values of these structures", the way that stress it mechanical becomes the bones densest and can later be measured by examinations of Óssea Density in study of the author.